2019
DOI: 10.1139/cjfr-2018-0138
|View full text |Cite
|
Sign up to set email alerts
|

A review of a new generation of wildfire–atmosphere modeling

Abstract: One of the first significant developments in wildfire modeling research was to introduce heat flux as wildfire line intensity (kW·m -1 ). This idea could be adapted to using weather station measurements, topography, and fuel properties to estimate rate of fire spread, shape, and intensity. This review will present, in an accessible manner, the next evolution in wildfire models. The new generation models use mechanistic combustion models and large-eddy simulation (LES) to define the flaming combustion and the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 49 publications
0
36
0
2
Order By: Relevance
“…Our approach exemplifies how scientific computing can leverage machine learning and hardware accelerators to improve simulations without sacrificing accuracy or generalization. machine learning | turbulence | computational physics | nonlinear partial differential equations S imulation of complex physical systems described by nonlinear partial differential equations (PDEs) is central to engineering and physical science, with applications ranging from weather (1,2) and climate (3,4) and engineering design of vehicles or engines (5) to wildfires (6) and plasma physics (7). Despite a direct link between the equations of motion and the basic laws of physics, it is impossible to carry out direct numerical simulations at the scale required for these important problems.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our approach exemplifies how scientific computing can leverage machine learning and hardware accelerators to improve simulations without sacrificing accuracy or generalization. machine learning | turbulence | computational physics | nonlinear partial differential equations S imulation of complex physical systems described by nonlinear partial differential equations (PDEs) is central to engineering and physical science, with applications ranging from weather (1,2) and climate (3,4) and engineering design of vehicles or engines (5) to wildfires (6) and plasma physics (7). Despite a direct link between the equations of motion and the basic laws of physics, it is impossible to carry out direct numerical simulations at the scale required for these important problems.…”
mentioning
confidence: 99%
“…Simulation of complex physical systems described by nonlinear partial differential equations (PDEs) is central to engineering and physical science, with applications ranging from weather ( 1 , 2 ) and climate ( 3 , 4 ) and engineering design of vehicles or engines ( 5 ) to wildfires ( 6 ) and plasma physics ( 7 ). Despite a direct link between the equations of motion and the basic laws of physics, it is impossible to carry out direct numerical simulations at the scale required for these important problems.…”
mentioning
confidence: 99%
“…He studied the rate of fire movement, predicted flame length, energy, and ecological impact, and concluded that Canadian models, including RedAPP and CanFIRE provide more accurate predictions than BehavePlus. Similarly, many tools exist for fire, and smoke models, which are crucial in decision making and planning to tackle the forest or a wild-land fire [74][75][76][77]. A lot of research has been done in the last two decades, especially after the increase of computation power during the last few years [77][78][79][80].…”
Section: Scope Of ML Algorithms In Forest Fire Management Frame-workmentioning
confidence: 99%
“…Similarly, many tools exist for fire, and smoke models, which are crucial in decision making and planning to tackle the forest or a wild-land fire [74][75][76][77]. A lot of research has been done in the last two decades, especially after the increase of computation power during the last few years [77][78][79][80]. Satellite active fire data such as Visible Infrared Imager Radiometer Suite (VIIRS) [81], moderate-resolution imaging spectro-radiometer (MODIS) [82] etc., can be vention and fighting [62,63].…”
Section: Scope Of ML Algorithms In Forest Fire Management Frame-workmentioning
confidence: 99%
“…In the past few decades, wildland and wildland-urban interface (WUI) fires have received substantial attention due to their destructive nature and extensive cost to lives and property [1][2][3]. A large body of literature can be found on the subject, as seen in various review articles [2,4,5]. Due to the complex nature of fire, limited computing resources, and the needs of planners and first responders, most models of wildfires have historically relied on simplified field-tested rules and correlations.…”
Section: Introductionmentioning
confidence: 99%